Microstructural investigation of plasma sprayed ceramic coatings focusing on the effect of the splat boundary for SOFC sealing applications using peridynamics. (April 2021) - Guski, V.; Verestek, W.; Rapp, D.; Schmauder, S.
Highlights: An image analysis procedure transfers the plasma-sprayed ceramic SEM image to simulation models. Peridynamics is employed to investigate the effective anisotropic mechanical behaviour of the plasma-sprayed ceramic. The splat boundary phase enhances the effective anisotropic mechanical behaviour. Peridynamics reveals characteristic crack pattern of plasma-sprayed ceramics. Abstract: The present study employs a continuum mechanics approach called peridynamics to investigate the deformation as well as the damage behaviour of a 2D microstructure obtained from a plasma sprayed ceramic coating used in solid oxide fuel cell (SOFC) sealing systems. Due to the production process, plasma sprayed ceramic materials possess typical microstructural features, such as globular pores, interlamellar pores as well as microcracks, which are orientated along the splat boundaries parallel or perpendicular to the spraying direction. Several studies postulated a splat interface or boundary, which influences the effective mechanical behaviour of such a microstructure without increasing the observable porosity. By means of an image analysis technique a splat interface was identified and considered as a separate phase in the simulation models. Based on this procedure, a microstructural model of a plasma sprayed ceramic coating of a SOFC sealing system is investigated. The simulation results are compared to experimental and analytical results. These micromechanical simulations show that structural defects influence the crack initiation as well as the crack propagation while interconnecting these defects. Typical crack mechanisms, such as crack deflection, crack shielding or multiple cracking, are observed. Additionally, an anisotropy of the effective mechanical properties is observed in this heterogeneous material, which is generally expected for plasma sprayed materials. As a result, considering the splat boundary in the simulations increases the anisotropy of the mechanical behaviour, decreases stiffness as well as the strength and influences the crack pattern strongly.